Peranan Gaya Kepemimpinan terhadap Motivasi Kerja dan Kinerja Karyawan PT. Jamsostek (Persero) Cabang Yogyakarta - Resy Wina Putra; Suhartini . (Sinergi: Kajian Bisnis dan Manajemen, 2012)
This study aims to determine the effect of leadership style is instructive, consultative, participative, and delegative jointly or partially on work motivation and employee performance, determine the effect of motivation on performance as well as determine the effect of motivation as a intervening variable between leadership styles on employee performance PT . Jamsostek (Persero) in Yogyakarta. The population in this study are permanent employees of PT. Jamsostek (Persero) Branch of Yogyakarta is located in Jln. Urip Sumoharjo 106 which are 32 employees. While the sample in this study using a census method for a total sample of 32 employees. Analytical model used in this study is a simple linear regression analysis and multiple linear regression analysis. The results found partial simultaneous leadership style and instructive, consultative, participative, and delegative to the motivation of employees of PT. Social Security Branch of Yogyakarta, There is a positive influence of motivation on the performance of employees of PT. Social Security Branch of Yogyakarta, There is a simultaneous influence of leadership style and a partial instructive, consultative, participative, and delegative on the performance of employees of PT. Social Security Branch of Yogyakarta, and the most influential leadership style is positively instructive to work motivation, whereas the most influential consultative leadership style positively to the performance of employees of PT. Social Security Branch of Yogyakarta.Keywords: leadership style, instructive, consultative, participative, delegative, motivation    and employee performance.